2018
DOI: 10.12659/msm.906973
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Laparoscopic and Conventional Methods on Lung Functions in Colorectal Surgery

Abstract: BackgroundWe aimed to compare the lung functions, complication rates, and durations of the hospital and intensive care unit stays of patients who had undergone laparoscopic colorectal resection and open colorectal resection.Material/MethodsIn this study, data were collected prospectively and then evaluated retrospectively. The study was carried out between January 2015 and November 2016 in 2 university hospitals. Pulmonary function tests (PFT) and chest radiography were performed in all patients preoperatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
(20 reference statements)
1
12
0
Order By: Relevance
“…Laparoscopic gastrectomy was found to be more effective than open gastrectomy in reducing intraoperative blood loss, post-operative complications, and reducing hospital stays [18,19]. However, the incidence of pulmonary complications did not differ from that of open gastrectomy [20]. In particular, upper abdominal surgery is a risk factor for post-operative pulmonary complications, and a systematic review reported an odds ratio of 2.91 (95% Confidence Interval: 2.35-3.60) [21].…”
Section: Discussionmentioning
confidence: 96%
“…Laparoscopic gastrectomy was found to be more effective than open gastrectomy in reducing intraoperative blood loss, post-operative complications, and reducing hospital stays [18,19]. However, the incidence of pulmonary complications did not differ from that of open gastrectomy [20]. In particular, upper abdominal surgery is a risk factor for post-operative pulmonary complications, and a systematic review reported an odds ratio of 2.91 (95% Confidence Interval: 2.35-3.60) [21].…”
Section: Discussionmentioning
confidence: 96%
“…However, laparoscopy was reported to be more reliable in terms of hospital stay and lung infections (14). Authors of this study showed that lung ventilation is better and that there is less pulmonary complication in In a study on 296 patients who underwent robotic gynecological operations, among all the study population only 5 patients (2%) experienced a pulmonary complication.…”
Section: Discussionmentioning
confidence: 92%
“…1,14,15 The lower risk of respiratory complications of the laparoscopic approach can be explained with better lung ventilation as a result of less incision pain in the postoperative period for laparoscopic surgery. 16 The mechanism of diminished ileus has been explained in the literature with activating a pro-inflammatory cascade within intestinal tissues with the end effect of suppression of bowel muscle function. 17,18 The laparoscopic approach could reduce the inflammatory process and decrease the risk of postoperative prolonged ileus.…”
Section: Discussionmentioning
confidence: 99%